Analisis Stuktur Modal dan Likuiditas Terhadap Kinerja Keuangan (Pada Sub Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019-2023) - Pebi; Yulaikah; Enji Azizi (Indonesia Economic Journal, 2025)
This study aims to comprehensively analyze the influence of capital structure and liquidity on financial performance in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Capital structure is measured using the Debt to Equity Ratio (DER), liquidity using the Current Ratio (CR), and financial performance using Return on Assets (ROA). The research method employed is quantitative with a multiple linear regression approach to evaluate the relationships between these variables both partially and simultaneously. The results reveal that capital structure and liquidity simultaneously have a significant effect on financial performance. Partially, capital structure has a significant negative impact on financial performance, indicating that an increase in debt relative to equity may reduce asset management efficiency and bank profitability. On the other hand, liquidity has a significant positive impact on financial performance, suggesting that higher short-term financial capability leads to better financial outcomes. This study provides important implications for bank management, investors, and regulators in determining optimal strategies for managing capital structure and liquidity to enhance profitability and financial stability, especially in the aftermath of the economic uncertainty caused by the pandemic.